Targeted gene editing and near-universal cDNA insertion of CYBA and CYBB as a treatment for chronic granulomatous disease - Jonas Holst Wolff; Thomas Wisbech Skov; Didde Haslund; Sofie Rahbek Dorset; Anne Louise S. Revenfeld; Clotilde Aussel; Sofie E. Jørgensen; Mette Holm; Martin K. Thomsen; Sandra Ammann; Toni Cathomen; Trine H. Mogensen; et al. (Nature Communications)
Abstract Chronic granulomatous disease (CGD) is a severe inborn error of immunity caused by NADPH oxidase defects. Here, we develop CRISPR/Cas9-based gene editing strategies for correction of variants in the CYBA and CYBB genes causing CGD. For X-linked CGD, we also develop a near-universal gene editing strategy by targeted integration of a truncated CYBB cDNA in CD34+ hematopoietic stem and progenitor cells (HSPCs). Throughout, off-target editing and chromosomal translocations are evident, which negatively impact the ability of gene-edited HSPCs to engraft in immunodeficient mice. However, by employing a high-fidelity Cas9 to minimize off-target editing, we demonstrate restoration of the multilineage engraftment potential of gene-edited HSPCs. Moreover, to further improve safety, we develop a D10A Cas9n editing approach with no detectable off-target activity or chromosomal translocations. Collectively, through risk assessments of different gene editing approaches, we present a D10A Cas9n-based strategy with improved safety, offering a potentially curative treatment for CGD patients.